Laporan reformasi Dewan Negara - Daud, Mahyuddin; Shuaib, Farid Sufian; Mohd Badrol Afandi, Nor Hafizah; Mohamad Amin, Noor Shuhadawati; Torla, Areej (2019)
report on the study by the working committee on the senate reform - to reinforce the Parliamentary independence and to enhance the role of the Senate